Pancreatic cystadenocarcinoma: Unusual clinical presentation and non-conventional operations - Hernández, José A; Lyonnet, Alberto; Colet, Andrés; Juambeltz, Carlos; Chiossoni, Martha; Estrugo, Roberto; Montano, Daniel; Praderi, Raúl (Cirugía del Uruguay, 1991)
The authors analyse four cases of pancreatic cystoadenocarcinoma whose clinical presentation was that of abdominal tumors, with sepsis in one case, upper digestive hemorrhage and choledocal syndrome in another. They suggest as ideal treatment duodenopancreatectomy with pancreatic exclusion of the remanen/ proposing as an alternative procedure tumoral mass reduction.